Involvement of women farmers in the agro-ecological transition and transformation of their work: Chronicle of the agricultural organization Groupe Femmes 44 - Serpossian, Emilie; Coquil, Xavier; Annes, Alexis (Frontiers in Sustainable Food Systems, 2022)
Women professional organizations appear as a resource for women to foster change in power relations on their farm. In this manuscript, we explore to what extent participation in a non-mixed professional organization named Groupe Femmes 44 contributed to transformations of women farmers' work. Particularly, we question the role of women farmers in the transition of their farming system toward agroecological principles and the conditions of their empowerment within their farm which allows these transitions. Our results show that Groupe Femmes 44 represents a socio-professional environment allowing women farmers to discuss, to put words and find answers on technical, communicational, organization as well as social issues. It allowed some participants to discover the existence, the relevance, and the more ecological dimension of self-sufficient and autonomous systems. Therefore, it stood as a key resource to foster professional transition toward these systems. For the women who were already involved in such systems, Groupe Femmes 44 contributes to the transition toward more equitable systems by questioning work organization and gender inequality.